The Conceptual Foundations of Relationship Marketing: Review and Synthesis - ShethJagdish N.; Parvatiyar, Atul; Sinha, Mona (Экономическая социология, 2015)
The present review is devoted to a rapidly developing area of marketing — relationship marketing. The authors suggest that the conceptual foundations of it are not currently well developed but forecast that it will transform into a discipline in the near future. They outline two approaches to the definition of relationship marketing and provide their own definition, emphasizing such aspects as collaboration, creation and enhancement of value for those who are involved in relationships. The authors trace the origins of relationship marketing, describing the importance of a range of factors that contribute to the increasing importance of relationship marketing today, such as the development of services, communication with the end consumer, etc. A section of this work examines the development of theoretical approaches: the authors argue that marketing originated in economics, which tended to ignore issues related to distribution systems. They also show that questions concerning relationship marketing were considered even before the term itself was introduced. In the final section, the authors touch upon the models that describe processes in relational marketing and analyze its components step-by-step. The authors highlight three core aspects of relational marketing: setting a purpose, choosing parties and program formation. In the conclusion the authors describe three possible levels of future studies in this area — the concept level, model level and process level — and specifics of each level are characterized.